Facile fabrication of magnetic covalent organic frameworks for magnetic solid-phase extraction of diclofenac sodium in milk. (15th June 2021) - Huang, Lijin; Shen, Rujia; Liu, Ruiqi; Xu, Shengrui; Shuai, Qin
Highlights: Magnetic covalent organic framework (MCOF) was prepared via a facile solvent-free approach. MCOF was effective for the extraction of diclofenac sodium. The proposed method exhibited a low limit of detection and superior linearity. The established method is of superior accuracy for the determination of diclofenac sodium in milk. Abstract: A robust magnetic solid-phase extraction (MSPE) method based on magnetic covalent organic framework (MCOF) coupled with high-performance liquid chromatography (HPLC)-ultraviolet (UV)/mass spectrometry (MS) was proposed for the determination of trace diclofenac sodium (DS) in milk. The prepared MCOF exhibited high extraction efficiency, which can be attributed to its high specific surface area as well as strong π-π and hydrophobic interactions between MCOF and DS. In addition, the potential influencing factors, including sample volume, adsorbent dosage, extraction time, and elution parameters, were fully estimated. The experimental results demonstrated that the established method was sensitive for the quantification of DS with high accuracy. Remarkably, the detection limit of DS was found to be 10 ng/kg under the optimal conditions. More impressively, the developed method was successfully applied to monitor trace DS in milk, demonstrating its outstanding durability and practical potential as an appealing method to regular monitor trace pharmaceutical contaminants in real food samples.